Home safe home: Evaluation of a childhood home safety program. Issue 3 (September 2016) - Stewart, Tanya Charyk; Clark, Andrew; Gilliland, Jason; Miller, Michael R.; Edwards, Jane; Haidar, Tania; Batey, Brandon; Vogt, Kelly N.; Parry, Neil G.; Fraser, Douglas D.; Merritt, Neil
Abstract : BACKGROUND: The London Health Sciences Centre Home Safety Program (HSP) provides safety devices, education, a safety video, and home safety checklist to all first-time parents for the reduction of childhood home injuries. The objective of this study was to evaluate the HSP for the prevention of home injuries in children up to 2 years of age. METHODS: A program evaluation was performed with follow-up survey, along with an interrupted time series analysis of emergency department (ED) visits for home injuries 5 years before (2007–2013) and 2 years after (2013–2015) implementation. Spatial analysis of ED visits was undertaken to assess differences in home injury rates by dissemination areas controlling differences in socioeconomic status (i.e., income, education, and lone-parent status) at the neighborhood level. RESULTS: A total of 3, 458 first-time parents participated in the HSP (a 74% compliance rate). Of these, 20% (n = 696) of parents responded to our questionnaire, with 94% reporting the program to be useful (median, 6; interquartile range, 2 on a 7-point Likert scale) and 81% learning new strategies for preventing home injuries. The median age of the respondent's babies were 12 months (interquartile range, 1). The home safety check list was used by 87% of respondents to identify hazards in their home, with 95% taking action to minimize the risk. The time series analysis demonstrated a significant decline in ED visits for home injuries in toddlers younger than2 years of age after HSP implementation. The declines in ED visits for home injuries remained significant over and above each socioeconomic status covariate. CONCLUSION: Removing hazards, supervision, and installing safety devices are key facilitators in the reduction of home injuries. Parents found the HSP useful to identify hazards, learn new strategies, build confidence, and provide safety products. Initial finding suggests that the program is effective in reducing home injuries in children up to 2 years of age. LEVEL OF EVIDENCE: Therapeutic/care management study, level V.